Preparation of Biodiesel from Waste Vegetable Oils Using Waste Eggshells as a Heterogeneous Catalyst (Latakia University Journal -Basic Sciences Series, 2022)
Biodiesel is an alternative fuel to petroleum diesel, the process of preparing it is an important topic at the time presently, in both practical and economic terms, it is prepared by using renewable, natural materials at low cost. In this paper, biodiesel was prepared by transesterification process using used vegetable oils and using a solid basic catalyst based on calcium oxide prepared from egg shells(eggshells were washed and calcined at 900 oC to prepare calcium oxide, which loaded with KCl by wet impregnation method). The effect of loading calcium oxide with KCl as an enhancer of basic properties on the reaction yield was studied. The research also included the study of the optimal conditions for the interaction, and the results were recorder the highest yield of biodiesel 92% at reaction conditions: the ratio of oil to alcohol (1:9) mol, catalyst ratio (2% of the oil weight), a temperature of  60 oC, and reaction time 120 min. The prepared biodiesel was confirmed by infrared spectroscopy (FTIR), the physical and chemical properties of the prepared biodiesel were also studied, and were in conformity with the American(ASTM) and European(EN) standards.